Spatial analysis of potential tourist sites in the district of Marco, province of Jauja, Junín - Acuña Caceres, Wendy Michel (2023)
The district of Marco, which is located in the province of Jauja in the Junín region of Peru, is a place of archaeological sites, famous for its ancient civilization and landscapes. Despite the existing tourism potential, the area has not been used for tourism. The research aims to identify indicators to determine the tourism potential, evaluate and propose a tourist route prioritizing areas for the development of sustainable tourism for the benefit of the populated centers: Marco, Tragadero, Hualiz, Muquillanqui and Huashua. For this analysis, ten spatial indicators were considered. In addition, the Geographic Information System (GIS) and the Hierarchical Analysis Process (AHP) were used to calculate the details of the spatial indicators and the weights. The results revealed the zoning of the tourism potential: Very High (PTMA) with 0.248 ≤ R ≤ 0.435; High (PTA) with 0.168 ≤ R ≤ 0.248; Medium (PTM) with 0.098 ≤ R ≤ 0.168 and low (PTB) with 0.051 ≤ R ≤ 0.098. The generated cartography allows to have a better field of spatial analysis for the management of the territory. Furthermore, it will be useful for planners and decision makers to formulate strategies for tourism development.